Enhanced biogas production and substrate degradation through the intermittent operation of modified upflow anaerobic sludge blanket–static granular bed reactor series. (6th August 2022) - Mariraj Mohan, S.; Swathi, T.
Abstract: In the present study, the performance of a modified upflow anaerobic sludge blanket (MUASB) reactor–static granular bed reactor (SGBR) series in intermittent operation was analyzed for the treatment of synthetic wastewater. The reactor series was operated with a hydraulic retention time (HRT) of 24 h. The maximum chemical oxygen demand (COD) removal and biogas production of the reactor series obtained during the intermittent operation were 99 ± 0.29% and 0.529 ± 0.03 m 3 /kg CODdigested, respectively. One‐way analysis of variance (ANOVA) indicated a significant difference in biogas production during continuous and intermittent operations, whereas the COD removal was similar. Intermittent operation of the reactor series yielded a 56.05% increase in biogas production when compared with the continuous operation. The reactor series was maintained stable throughout the operational period. The maximum total suspended solids (TSS) removal and total nitrogen (TN) removal of the reactor series during the intermittent operation were 91.67% and 72.37%, respectively. Intermittent operation of the reactor series can be considered advantageous because of the reduced operational cost and enhanced biogas production in addition to COD removal. Practitioner Points: Intermittent operation of MUASB–SGBR series in terms of COD removal is evaluated. COD removal of reactor series was similar in intermittent and continuous operation. Biogas production in intermittent operation was superior to continuous operation. Reactor series performance is also compared with continuous operation using one‐way ANOVA. Abstract : The MUASB–SGBR series when operated in intermittent mode was found to enhance the biogas production when compared with continuous operation. The adaptation of granules in MUASB reactor and SGBR during the feed and feed‐less period would have contributed to the stability and robustness of the reactor series.